2013
DOI: 10.1093/carcin/bgt014
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin β receptor mediates caspase-dependent tumor cell apoptosis in vitro and tumor suppression in vivo despite induction of NF-κB activation

Abstract: Ligation of the lymphotoxin β receptor (LTβR) has been shown to induce both tumor growth inhibition and promotion. The functions of LTβR in these two contrasting cellular processes require further study. We demonstrated here that mice deficient in LTβR ligands, LTα, LIGHT or both LTβ and LIGHT, exhibit greater susceptibility to methylcholanthrene-induced tumor development. LTα, LTβ and LIGHT were expressed in tumor-infiltrating immune cells, and LTβR was expressed on human colon carcinoma and soft tissue sarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…With regard to caspases, a family of aspartate-specific cysteine proteases, it has been reported that the activation of caspase cascade appears to be directly responsible for many agents to induce apoptosis in many types of cancer cells [30,31]. Caspases are classified based on their mode of activation as either initiator or effector caspases.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to caspases, a family of aspartate-specific cysteine proteases, it has been reported that the activation of caspase cascade appears to be directly responsible for many agents to induce apoptosis in many types of cancer cells [30,31]. Caspases are classified based on their mode of activation as either initiator or effector caspases.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is an effective mimic of the normal cell surface ligand and its properties have been described. 37 BS1 was a gift from Biogen (Cambridge, MA). RNA was isolated from these cultures after 24 hours and subjected to either quantitative PCR using TaqMan primers or a custom human gene specific 78 gene Nanostring array effectively as described.…”
Section: Dermal Fibroblast Culturesmentioning
confidence: 99%
“…77 Both antibodies have been extensively analyzed and used previously. 78,79 In situ hybridization for LTb RNA in situ hybridization was performed using the RNAscope 2.0 brown FFPE Assay (Advanced Cell Diagnostic, Hayward, CA) according to the manufacturer's protocol. Slides were mounted using EcoMount mounting medium (BioCare Medical, Berlin, Germany) and analyzed using LEICA SCN400 Slide scanner (Leica Microsystems, Wetzlar, Germany).…”
Section: Cell Culturementioning
confidence: 99%